Strategi Pengembangan MSDM Untuk Meningkatkan Kinerja Dan Motivasi Karyawan - Dahlia Ayu Sulistiani; Mawaddah Azkiya Syarifatunnisa; Vina Nut Fitriah (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
Human resource management is one of the most important factors in the success of an organization. Proper strategic planning in HR management can help increase employee motivation and productivity. The purpose of this study is to understand the strategies used by Human Resource Management to improve employee motivation and performance efficiency. The research findings show that strategies such as training and development programs, leadership style, and transparency have a significant impact on employee motivation and performance. This can be interpreted that a holistic approach in HRM development is essential to increase employee motivation and productivity.